Management of arrhythmias in athletes: Atrial fibrillation, premature ventricular contractions, and ventricular tachycardia - Lai, E.; Chung, E. H. (Current Treatment Options in Cardiovascular Medicine, 2017)
Management of atrial fibrillation, premature ventricular contractions, and ventricular tachycardia without underlying cardiac disease or arrhythmogenic conditions differs in athletes from the general population. Athletes tend to be younger, healthier individuals with few comorbidities. Therapies that work well in the general population may not be appropriate or preferable for athletes. Management strategies include deconditioning, pharmacologic therapy, such as rate control with ß-blockers or non-dihydropyridine calcium channel blockers and rhythm control with class I or class III antiarrhythmic drugs, and catheter ablation. Deconditioning is not preferred by athletes because of lost playing time. Pharmacologic therapy is well tolerated among most individuals, but is not as favorable in athletes. Rate control medications can reduce performance and ß-blockers, in particular, are prohibited in many sports. Antiarrhythmic drugs are preferred over rate control with athletes, but many, especially younger athletes, may not like the idea of long-term medical therapy. Catheter ablation has been proven to be safe and efficacious, may eliminate the need for long-term medical therapy, and is supported by the major societies (AHA, ACC, ESC).